Challenges and Opportunities of South Africa’s Electronic Vaccination Data System in the Provision of COVID-19 Vaccines - Hofisi, Costa; Chigova, Lewis Edwin (International Journal of Criminology and Sociology, 2021)
The increase in the development and availability of COVID-19 vaccines has resulted in countries developing strategies to inoculate their populations. The Government of South Africa, for example, developed the Electronic Vaccination Data System (EVDS) in a bid to swiftly monitor the distribution and administration of vaccines in the country. The EVDS allows the government to keep track of all the vaccinated people and makes it easy for the Department of Health to capture all important data related to the country’s COVID-19 vaccination program. However, very few studies have explored the potential challenges and opportunities presented by the EVDS. The pertinent question remains: To what extent does the EVDS enable the South African government to provide vaccinations to all citizens without leaving anyone behind? In answering this research question, this paper seeks to use desktop research and extensive literature review to explore a constellation of factors that can present both challenges and opportunities of using the EVDS in South Africa. The paper argues that the following factors are possible challenges to the EVDS: lack of information, technical barriers, information communication technology literacy gaps, and vaccine apartheid. It also makes a case that the EVDS provides the government with possibilities and opportunities in decision support, logistics management, and vaccine administration. The paper recommends that the EVDS platform be complemented by other strategies to provide vaccines to the poor and vulnerable population members.